Response of sesame (Sesamum indicum) varieties to dates of sowing during rainy season - PATRA, A K (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted at Chiplima. Orissa, during the rainy season of 1996-98 to study the performance of 10 varieties (’Vinayak’, ’Usha’, ’Kanak’, ’OTM 10’, ’OTM II’, ’Uma’, ’Kalika’, ’Krishna’, ’B 67’ and ’Balangir Local’) of sesame (Sesamum indicum L.) under 2 dates of sowing (25 June and 15 July). Varieties varied significantly with respect to growth and yield attributes, viz plant height, branches/plant, capsules/plant, and seed yield and oil yield. ’Kalika recorded the maximum seed yield (890 kg/ha). The crop sown on 15 July showed a reduction of 8.5% in seed yield compared with that sown on 25 June.